2005
DOI: 10.1111/j.1365-2567.2005.02241.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes modulate cytokine release from dendritic cells

Abstract: Summary Leukotriene B4 (LTB4) and cysteinyl leukotrienes (CysLTs) are known as potent mediators of inflammation, whereas their role in the regulation of adaptive immunity remains poorly characterized. Dendritic cells (DCs) are specialized antigen‐presenting cells, uniquely capable to initiate primary immune responses. We have found that zymosan, but not lipopolysaccharide (LPS) stimulates murine bone marrow‐derived dendritic cells (BM‐DCs) to produce large amounts of CysLTs and LTB4 from endogenous substrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 47 publications
1
36
1
6
Order By: Relevance
“…More precisely, we observed a correlation between IL-10 and the presence of T cells, although not specifically with T reg . A possible explanation for this observation could be that other cells, like M. tuberculosis-infected dendritic cells and macrophages, express IL-10, particularly in the presence of effector T cells (20,21). Despite significant differences in protection and T cell responses, histological analyses revealed similar granuloma shape, size, and numbers between infected C57BL/6 wt and T cellreconstituted Rag1…”
Section: Resultsmentioning
confidence: 90%
“…More precisely, we observed a correlation between IL-10 and the presence of T cells, although not specifically with T reg . A possible explanation for this observation could be that other cells, like M. tuberculosis-infected dendritic cells and macrophages, express IL-10, particularly in the presence of effector T cells (20,21). Despite significant differences in protection and T cell responses, histological analyses revealed similar granuloma shape, size, and numbers between infected C57BL/6 wt and T cellreconstituted Rag1…”
Section: Resultsmentioning
confidence: 90%
“…23 Zymosan, a Toll-like receptor 2 agonist, but not lipopolysaccharide (LPS), a classic Toll-like receptor 4 agonist, stimulates the production of CysLT by DCs. 24,25 Despite these observations, their impact on cytokine production by DCs is unclear. In spite of the close relationship between mast cells and DCs in mucosal epithelium and skin, little progress has been made regarding the impact of CysLT on the genesis of DCs.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 97%
“…In addition, pretreatment of patients with mild asthma using a CysLT1 antagonist decreased the number of circulating myeloid DCs, demonstrating a significant role of cysLTs in DC trafficking in vivo (29). Finally, a recent study showed that LTs can modulate cytokine release from DCs (30). Despite these observations, LT receptor expression in DC has not been extensively examined.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 95%